Materials challenges in alternative and renewable energy : a collection of papers presented at the Materials Challenges in Alternative and Renewable Energy Conference February 21-24, 2010, Cocoa Beach, Florida - Energy 2010 (2nd : Cocoa Beach, Fla.); Wicks, George G.; American Ceramic Society (Hoboken, N.J. : Wiley ; [Westerville, Ohio] : American Ceramic Society)
Includes bibliographical references and author index